2015
DOI: 10.1371/journal.pone.0135243
|View full text |Cite
|
Sign up to set email alerts
|

A New Dimension in Documenting New Species: High-Detail Imaging for Myriapod Taxonomy and First 3D Cybertype of a New Millipede Species (Diplopoda, Julida, Julidae)

Abstract: We review the state-of-the-art approaches currently applied in myriapod taxonomy, and we describe, for the first time, a new species of millipede (Ommatoiulus avatar n. sp., family Julidae) using high-resolution X-ray microtomography (microCT) as a substantive adjunct to traditional morphological examination. We present 3D models of the holotype and paratype specimens and discuss the potential of this non-destructive technique in documenting new species of millipedes and other organisms. The microCT data have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 39 publications
0
81
0
Order By: Relevance
“…We chose to describe both species integratively (Padial et al 2010), using drawings and scanning-electron microscopy (Oatley et al 1966) combined with genetic barcoding (Hebert et al 2003;Hebert & Gregory 2005). For only the second time in Diplopoda taxonomy (Akkari et al 2015), we also use micro-CT technology (Ritman 2004) to study and visualize internal structures non-invasively. …”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…We chose to describe both species integratively (Padial et al 2010), using drawings and scanning-electron microscopy (Oatley et al 1966) combined with genetic barcoding (Hebert et al 2003;Hebert & Gregory 2005). For only the second time in Diplopoda taxonomy (Akkari et al 2015), we also use micro-CT technology (Ritman 2004) to study and visualize internal structures non-invasively. …”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…Already Akkari et al (2015) showed the great potential of micro-CT in millipede taxonomy. It can be used to visualize and infer internal morphological characters, which can be exploited not only for the species description itself, but also for subsequent morphological phylogenetic reconstruction as demonstrated by Blanke & Wesener (2014).…”
Section: Micro-ct In Taxonomy and Phylogenymentioning
confidence: 99%
“…However, long‐lasting online repositories such as Digital Morphology Library (http://www.digimorph.org), Dryad Digital Repository (http://datadryad.org), MorphoBank (https://morphobank.org), MorphoSource (http://morphosource.org), and Science3D (https://www.science3d.org) provide storage facilities to ease the publication of datasets and accessibility to the scanned specimens. Outstanding examples of this possibility are the cybertypes of recently described species (Akkari et al., 2015) and online repositories of fossils (UMORF, https://umorf.ummp.lsa.umich.edu/). …”
Section: Processing Of X‐ray Ct Imagesmentioning
confidence: 99%
“…Fields such as taxonomy (Akkari, Enghoff, & Metscher, 2015; Faulwetter, Vasileiadou, Kouratoras, Dailianis, & Arvanitidis, 2013; Fernández, Kvist, Lenihan, Giribet, & Ziegler, 2014) and morphology (Mattei, Riccio, Avila, & Wolfner, 2015; Wipfler et al., 2016) have greatly benefited from μ‐CT technique. However, most studies to date have focused on in‐depth studies of single individuals, and organisms′ responses to environmental drivers were only rarely considered.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses that use the number of authors per species description as a proxy for effort [19] ignore the global trend for an increasing number of authors per paper [2], and assume that the effort required per species description has remained constant over time. An alternative interpretation is that the quality of taxonomic description is increasing over time [36], reflecting both increased thoroughness and the availability of new technologies [37,5]. Rather than try and estimate an unknown (the number of species remaining to be described), here I focus on the current state of taxonomic knowledge.…”
Section: Taxonomymentioning
confidence: 99%